A method to stabilise the performance of negatively fed KM3NeT photomultipliers. (19th December 2016) - Adrián-Martínez, S.; Ageron, M.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, G.; Ardid, M.; Avgitas, T.; et al.
Abstract: The KM3NeT research infrastructure, currently under construction in the Mediterranean Sea, will host neutrino telescopes for the identification of neutrino sources in the Universe and for studies of the neutrino mass hierarchy. These telescopes will house hundreds of thousands of photomultiplier tubes that will have to be operated in a stable and reliable fashion. In this context, the stability of the dark counts has been investigated for photomultiplier tubes with negative high voltage on the photocathode and held in insulating support structures made of 3D printed nylon material. Small gaps between the rigid support structure and the photomultiplier tubes in the presence of electric fields can lead to discharges that produce dark count rates that are highly variable. A solution was found by applying the same insulating varnish as used for the high voltage bases directly to the outside of the photomultiplier tubes. This transparent conformal coating provides a convenient and inexpensive method of insulation.